Agricultores familiares produtores de mamona no Ceará: nível tecnológico e seus determinantes - Gonçalves, Marcos Falcão (2011)
The depletion of fossil fuels has led them to search for alternative sources of energy. In this context the Brazilian government launched the National Program of Biodiesel Production and Use _ PNPB, taking advantage of natural conditions conductive to the production of ethanol, based on the principle of inclusion of family farming. In line with the federal program, the Government of Ceará also launched its incentive program, initially selected as castor oilseed primary, which makes us think about the real ability to integrate these farmers, as well as the level of technology used by them. The objective of this work is to identify the technological level of producers of castor farmers in Ceará and its determinants. For the preparation of this study used primary data obtained through the application of questionnaires to 100 farmers and 50 castor farmers who do not cultivate this culture. The questionnaires were administered in five municipalities with the highest concentration of soybean fields, from the December/2009 January/2010. The results show that 80% of producers are part of the working age population, while 97% are male and acquire their income in agriculture. Concerning the technological level, using the Logit model to identify the determinants for adoption, it was found that the producers of castor evaluated using an average of 59% of recommended technologies, are classified in pattern II. It is noteworthy that the origin of seed plants by the number of pits and the consortium of crops were the predominant technology for achieving this result. As determinants of technology adoption, age and years of study were the most significant variables. Thus, it is concluded that they needed guidance and support given to producers of castor to improve productivity and profitability of the crop.